2021
DOI: 10.1080/08952841.2021.1965456
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mental well-being, risk and protective factors among older lesbians /gay women in the United Kingdom during the initial COVID-19 2020 lockdown

Abstract: This article reports on a subset of findings from a recent UK survey of the impact of COVID-19 on older LGBT+ people in the UK. It considers the responses of 149 lesbian/gay women (137 cisgender, 12 trans) to questions relating to physical and mental health and wellbeing. Findings indicate that those women -in couples and singles -who were happy with their living circumstances pre-COVID showed stoicism, adaptability, and determined positivity in response to the pandemic and associated lockdown. Some even repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Future studies that investigate whether pandemics worsen inequalities for sexual minorities would provide firmer ground for interpretation. Notwithstanding, findings from this study still add to the growing literature on health disparities and aging populations in times of a national, public health crisis ( Walubita et al, 2021 ) and a small but growing literature on the health and well-being of sexual minority adults worldwide (e.g., Barrientos et al, 2021 ; Hafford-Letchfield et al, 2021 ; Westwood et al., 2021 ).…”
Section: Discussionmentioning
confidence: 51%
“…Future studies that investigate whether pandemics worsen inequalities for sexual minorities would provide firmer ground for interpretation. Notwithstanding, findings from this study still add to the growing literature on health disparities and aging populations in times of a national, public health crisis ( Walubita et al, 2021 ) and a small but growing literature on the health and well-being of sexual minority adults worldwide (e.g., Barrientos et al, 2021 ; Hafford-Letchfield et al, 2021 ; Westwood et al., 2021 ).…”
Section: Discussionmentioning
confidence: 51%
“…These areas will need to be prioritised by the government in the pursuit of LGBT+ equalities agenda if it wishes to provide high quality health and care services, improve population health and make good on its promises to 'level up' society (Cameron et al, 2021). Change must sit in a wider strategy that supports investment in tackling LGBT+ health inequalities (Westwood, Hafford-Letchfield and Toze, 2021) and not least, the role of social workers in supporting community development and promoting the needs of vulnerable marginalised groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some research findings into the experiences of LGBT+ older people during lockdown in the UK demonstrated that the impacts of COVID-19 have been mixed and differentiated for specific sub-populations (Hafford-Letchfield, Toze and Westwood, 2021;Westwood, Hafford-Letchfield and Toze, 2021;Toze, Westwood and Hafford-Letchfield, 2021). Lockdown appeared to have magnified LGBT+ older people's overall experiences, for example those people happy with their living circumstances prior to COVID, reported stoicism, adaptability and determined positivity and some even reported an improved quality of life, better personal relationships and increased neighbourly support (Westwood, Hafford-Letchfield and Toze, 2021). There were some gender differences in that gay men placed a stronger emphasis on independence, distinguishing between social contacts and the provision of support (Westwood, Hafford-Letchfield and Toze, 2021a).…”
Section: Lesbian Gay Bisexual and Trans Ageingmentioning
confidence: 99%
“…Theme 2: Loss of Social and Kinship Connection. The loss of social and kinship connection was reported across eight articles (Braksmajer & London, 2021;Gaspar et al, 2021;O'Brien et al, 2021;Pereira et al, 2021;Philpot et al, 2021;Quinn et al, 2021;Riggle et al, 2021;Westwood et al, 2021). This type of loss largely related to losses in the quality and quantity of friendships, LGBTQ+ people's Family of Choice, their Family of Origin and romantic or sexual partners (Wheat & Thacker, 2019).…”
Section: Inductive Thematic Synthesismentioning
confidence: 99%